2022
DOI: 10.3389/fonc.2022.976577
|View full text |Cite
|
Sign up to set email alerts
|

The oncogenic roles of JC polyomavirus in cancer

Abstract: JC polyomavirus (JCPyV) belongs to the human polyomavirus family. Based on alternative splicing, the early region encodes the large and small T antigens, while the late region encodes the capsid structural proteins (VP1, VP2, and VP3) and the agnoprotein. The regulatory transcription factors for JCPyV include Sp1, TCF-4, DDX1, YB-1, LCP-1, Purα, GF-1, and NF-1. JCPyV enters tonsillar tissue through the intake of raw sewage, inhalation of air droplets, or parent-to-child transmission. It persists quiescently in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 130 publications
(66 reference statements)
0
13
0
Order By: Relevance
“…We failed to detect p53 at the DNA, RNA, and protein level in our tumor specimen. As previously described, the C-terminal region of LTAg can interact with p53 (Zheng et al 2022) although inactivation of p53 is not absolutely required for polyomaviruses to induce cancer as shown for MCPyV and MCC. In fact, the LTAg expressed in MCPyV-positive MCC lacks the p53 binding domain but retains the Rb domain (DeCaprio 2021), as observed in our case.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…We failed to detect p53 at the DNA, RNA, and protein level in our tumor specimen. As previously described, the C-terminal region of LTAg can interact with p53 (Zheng et al 2022) although inactivation of p53 is not absolutely required for polyomaviruses to induce cancer as shown for MCPyV and MCC. In fact, the LTAg expressed in MCPyV-positive MCC lacks the p53 binding domain but retains the Rb domain (DeCaprio 2021), as observed in our case.…”
Section: Discussionmentioning
confidence: 73%
“…The early region encodes for nonstructural proteins, large T antigen (LTAg), small t antigen (stAg), and T'135, T'136, and T'165 proteins involved in the regulation of the virus cycle and in cell transformation (Frisque et al 1984;Khalili 2001). The N-terminal region of LTAg can interact with members of the retinoblastoma (Rb) protein family, whereas the C-terminal domain can bind p53 (Zheng et al 2022). The interaction with these tumor suppressors induces progression of the cell cycle and is a major feature of the oncogenic properties (Del Valle et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a study that reported the detection of archetype strain sequences in two cases of oligodendroglioma ( 50 ). The detection of JCPyV-DNA was previously reported in many different tumors, such as cervical, colorectal, gastric, lung, breast, brain, and urothelial cancers ( 17 23 ). Infection with JCPyV has been suggested to be associated with bladder carcinoma, which still remains a controversial hypothesis ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 84%
“…JCPyV large tumor antigen (LTAg) is located in the early region and has shown the capability to bind specifically with the p53 protein and retinoblastoma (pRB) protein, as known for some of the human polyomaviruses (HPyVs) ( 14 16 ). The presence of JCPyV-DNA was previously reported in many different tumor tissues, such as cervical, colorectal, gastric, lung, breast, brain, and urothelial cancers ( 17 23 ). The current number of members of HPyVs detected in various types of cancers has recently risen.…”
Section: Introductionmentioning
confidence: 76%
“…JCPyV may also be transmitted via the fecal–oral route. JCPyV infection rates within populations have been monitored using community sewage surveillance, as the virus is readily found in urine and stool [ 9 , 68 , 69 , 70 , 71 ]. During the coronavirus disease 2019 (COVID-19) pandemic, social and contact isolation protocols have decreased the transmission of respiratory-borne illnesses, including rhinovirus, influenza, and respiratory syncytial virus [ 72 ].…”
Section: How Is Jcpyv Transmitted?mentioning
confidence: 99%